المركز القانوني للمرقي العقاري في التشريع الجزائري - جروني, فايزة; بوساحة, نجاة (University of Eloued جامعة الوادي, 2021)
يلعب المرقي العقاري دورا مهما في نشاط الترقية العقارية، فهو من يبادر بالمشاريع العقارية، ويسهر على إدارتها وتسييرها بالتنسيق مع المتدخلين في المشروع العقاري من أجل حصول مقتني العقار على السكن، وبالنظر للمركز القانوني الذي يحتله المرقي العقاري فقد تدخل المشرع بموجب القانون رقم:11/04 الذي يحدد القواعد التي تنظم نشاط الترقية العقارية والنصوص القانونية المنظمة له بوضع ضوابط قانونية لاكتساب صفة المرقي العقاري لممارسة هذه المهنة. كما أخضعه للعديد من الالتزامات التي يسهر على احترامها وفي حالة الإخلال بها حمله الجزاء من خلال فرض عقوبات إدارية وأخرى جزائية.The real estate promoter plays an important role in the real estate promotion activity since he is the one in charge of initiating real estate projects and insuring their management, and coordinating with those involved in the project for the real estate acquirers to obtain housing. Regarding the legal status of the real estate promoter, according to Law No. 11 / 04 which defines the rules and the legal texts regulating the real estate promotion activity, the legislator has intervened by setting legal terms to acquire the status of a real estate promoter and practice this profession. It also assigned many obligations to him that should be respected, under the liability of administrative and other penal sanctions.
The Legal Status of the Real Estate Promoter in the Algerian Legislation
مقال
Keywords: المرقي العقاري، الحصول على الاعتماد، الالتزامات، العقوبات الإدارية، العقوبات الجزائية.; المرقي العقاري، الحصول على الاعتماد، الالتزامات، العقوبات الإدارية، العقوبات الجزائية.